Impact of Bioclogging on Peat vs. Sand Biofilters. Issue 6 (20th March 2015) - Mostafa, M.; Van Geel, P.J.
Abstract : Biological clogging of unsaturated soils is an important process that can lead to the development of a biomat and failure of biofilters used to treat various wastewater streams. Septic beds and peat filters used to treat septic tank effluent are important applications. Several conceptual models have been developed to simulate clogging in saturated soils; however, limited effort has been conducted to develop similar models for unsaturated soils. Different conceptual models have been proposed to simulate biological clogging in unsaturated systems. These models include the impacts of biomass growth on the relative permeability term for unsaturated flow, but limited experimental data have been used to validate these models. In this study, column experiments were conducted to study the clogging process in loose and dense peat, filter media sand, and septic bed sand. Experimental data indicated that the pore structure of the peat, in comparison to two commonly used sands for septic drainage fields, allowed the biomass to distribute itself over a greater depth within the peat biofilter and delayed the formation of a biomat at the surface and eventual clogging of the filter medium.